Reason and Timing for Conversion to Sternotomy in Robotic-Assisted Coronary Artery Bypass Grafting and Patient Outcomes. Issue 6 (November 2018) - Christidis, Nickolas K.; Fox, Stephanie A.; Swinamer, Stuart A.; Bagur, Rodrigo; Sridhar, Kumar; Lavi, Shahar; Iglesias, Ivan; Bainbridge, Daniel; Jones, Philip M.; Harle, Christopher C.; Chu, Michael W. A.; Teefy, Patrick; et al.
Objective: Conversion to sternotomy is a primary bailout method for robotically assisted coronary artery bypass grafting procedures. The aims of this study were to identify the primary reasons for conversion from robotically assisted coronary artery bypass grafting to sternotomy and to evaluate the in-hospital outcomes in such patients. Methods: Prospectively collected data from February 2004 to April 2017 were reviewed for 72 patients (56 men; mean age = 63.8 years) who required conversion to sternotomy during a robotically assisted coronary artery bypass grafting procedure with planned endoscopic left internal thoracic artery harvest and anastomosis to the left anterior descending on the beating heart. Results: The overall rate of conversion was 12.4% (72/581). Conversions occurred either during attempted endoscopic left internal thoracic artery harvest (31.9%), during endoscopic left anterior descending isolation (40.3%), during manual isolation and anastomosis of the left anterior descending (19.4%), or after anastomosis due to unsatisfactory flow (8.3%). Overall, the most common reason for conversion was an intramyocardial left anterior descending (43.1%). The median stay in the intensive care unit was 1 day (range = 0–20) and the median hospital length of stay was 5 days (range = 3–43). In-hospital complications included new atrial fibrillation (16.7%), need for blood transfusion (20.8%), mediastinitis (4.2%), postoperative myocardial infarction (2.8%), exploration for bleeding (2.8%), and 1 in-hospital death. Conclusions: The reasons for conversion were primarily related to anatomical factors that created difficulties for endoscopic left internal thoracic artery harvesting and left anterior descending identification. Patients who required conversion to sternotomy from robotically assisted coronary artery bypass grafting demonstrated acceptable outcomes and low complication rates.